THE ROLE OF TEACHING ENGLISH TO CHILDREN IN KINDERGARTENS - Boboyeva Sarvinoz (Galaxy International Interdisciplinary Research Journal, 2023)
In today’s modern society, learning English is becoming more and more popular. This article describes the role of the English language in our modern life and the importance of teaching it to young children in pre-school educational institutions (kindergartens) and the opinion of European scientists about it. Teaching English to children at an early age has a special place for this language to become more popular and widely used in the future, and teaching English to children as a second language from a young age is the basis for their future knowledge.